2015
DOI: 10.1590/1516-4446-2014-1540
|View full text |Cite
|
Sign up to set email alerts
|

The construct of psychopathy in a Chilean prison population

Abstract: Objective: To test the four-factor model of the Hare Psychopathy Checklist -Revised (PCL-R) empirical construct of psychopathy in a Chilean prison population by using instruments that supply different types of data. Methods: Two hundred and nine male inmates of the Prison of Los Andes, Chile, were evaluated. Confirmatory factor analysis was carried out with the PCL-R and the Self-Report of Psychopathy -IIIShort Form (SRP-III-SF). Conclusions:The results obtained with the PCL-R and the SRP-SF showed adequate f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 22 publications
3
28
0
3
Order By: Relevance
“…Although empirical studies have consistently demonstrated that increased PCL-R scores can predict violence and general recidivism (Dhingra & Boduszek, 2013;Salekin et al, 1996), the instrument's construct validity has recently been challenged Skeem & Cooke, 2010a, b). Inconsistencies have also been reported regarding the factor structure of the measures, with some researchers suggesting two-(e.g., McDermott et al, 2000;Medina et al, 2013), three-(e.g., Cooke et al, 2005a, b), four-(e.g., Freeman & Samson, 2012;León-Mayer et al, 2015;Neumann et al, 2013Zwets et al, 2015), and bi-factor (e.g., Debowska et al, 2014;FloresMendoza et al, 2008;Patrick et al, 2007) models to best capture the PCL-R and SRP-III/SF ratings. In spite of this conflicting evidence, there is a lack of a critical review of such research.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although empirical studies have consistently demonstrated that increased PCL-R scores can predict violence and general recidivism (Dhingra & Boduszek, 2013;Salekin et al, 1996), the instrument's construct validity has recently been challenged Skeem & Cooke, 2010a, b). Inconsistencies have also been reported regarding the factor structure of the measures, with some researchers suggesting two-(e.g., McDermott et al, 2000;Medina et al, 2013), three-(e.g., Cooke et al, 2005a, b), four-(e.g., Freeman & Samson, 2012;León-Mayer et al, 2015;Neumann et al, 2013Zwets et al, 2015), and bi-factor (e.g., Debowska et al, 2014;FloresMendoza et al, 2008;Patrick et al, 2007) models to best capture the PCL-R and SRP-III/SF ratings. In spite of this conflicting evidence, there is a lack of a critical review of such research.…”
Section: Discussionmentioning
confidence: 99%
“…Although the dimensionality of the PCL-R and its derivatives remains debatable, we found a significant number of studies to assess one possible solution (e.g., Declercq et al, 2015;León-Mayer et al, 2015;Neumann et al, 2013, even when fit indices for the tested model were below the recommended values (such as in studies by Mokros et al, 2011;Zwets et al, 2015). Of questionable value is also research where fit statistics were reported selectively (e.g., Gordts et al, in press;Vitacco et al, 2005;Zwets et al, 2015) or not reported at all (e.g., Medina et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous factor analytic work revealed a good fit for the four-factor model of the SRP-SF (e.g., Declercq, Carter, & Neumann, 2015;León-Mayer, Folino, Neumann, & Hare, 2015).…”
Section: Methodsmentioning
confidence: 96%